2017
DOI: 10.3389/fpsyg.2017.00505
|View full text |Cite
|
Sign up to set email alerts
|

Employee Wellbeing: Evaluating a Wellbeing Intervention in Two Settings

Abstract: This research presents two studies conducted to evaluate the Wellbeing Game in two different contexts: In a student sample and in an organizational setting. Study 1 investigated the efficacy of the Wellbeing Game, in terms of its effect of wellbeing, stress, and an image valence test, among 60 university students. The results showed that after playing the Wellbeing Game, students reported a significant positive change in wellbeing compared to those who did not play the Wellbeing Game, but there was no decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 40 publications
(67 reference statements)
1
56
0
Order By: Relevance
“…The definitions shifted from early characterizations in broad affective terms to more articulate, conceptually sharper ones (30), which provide relatively robust and consistent frameworks necessary for a scientific analysis (16). For example, consideration of job and life satisfaction is now combined in notions of employee well-being (31-33) and more well-being interventions are proposed to ensure that workers are both happy (or high in well-being) and productive (have high performance) (34,35).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The definitions shifted from early characterizations in broad affective terms to more articulate, conceptually sharper ones (30), which provide relatively robust and consistent frameworks necessary for a scientific analysis (16). For example, consideration of job and life satisfaction is now combined in notions of employee well-being (31-33) and more well-being interventions are proposed to ensure that workers are both happy (or high in well-being) and productive (have high performance) (34,35).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An evaluation study of a gamified web application showed a significant positive change in wellbeing of university students and employees of a financial organization in New Zealand compared to a control group [42]. Further, a study by Hull from 2009 [39] showed promising results using therapy video games to improve the wellbeing status of children.…”
Section: Gamification For Mental Health and Wellbeingmentioning
confidence: 99%
“…TWBG uses game design elements to motivate the users to participate in the game, such as badges, leaderboards, and point systems. After playing the game, users showed higher awareness for possibilities to promote their wellbeing [44], as well as lower stress levels and better wellbeing, compared to non-players [42]. However, as TWBG was only applied in New Zealand, its transferability to other countries and cultures remains unknown.…”
Section: The Wellbeing Gamementioning
confidence: 99%
“…Another happiness index dimension with almost the same definition as positive emotions is job-related well-being. However, it is related to energy, inspiration, fulfilment and excitement (Bakker & Oerlemans, 2011;Keeman, Naswall, Malinen & Kuntz, 2017;Kirsten, Van der Walt & Viljoen, 2009;Rodríguez & Sanz, 2013), which leads to organizational success (Page & Vella-Brodrick, 2009). The study conducted by Warr and Inceoglu (2017), which comprised of two groups, found no significant differences between them in relation to wellbeing.…”
Section: Job-related Wellbeingmentioning
confidence: 99%